IMPLEMENTASI TEKNIK PEMBELAJARAN KARYA WISATA DALAM MENINGKATKAN HASIL BELAJAR PESERTA DIDIK: SDN KALIANYAR 2 KECAMATAN TAMANAN KABUPATEN BONDOWOSO (Mitra Pendidikan, 2020)
The use of learning techniques in the proper learning process is needed to achieve the expected learning objectives. If the use of learning techniques is neglected, it will affect student learning outcomes. The purpose of this research is to improve student learning outcomes with field trip techniques. The method used is through self-reflection, with the aim of improving performance as a teacher so that student learning outcomes increase. The results obtained from this study are the use of field trip techniques to improve student learning outcomes. This is evidenced by the increase in student learning outcomes. The criterion for the success of using this method is to get good learning achievement, which is indicated by students getting a score above the predetermined minimum requirement. This activity is carried out in 2 cycles.